Relevance of internal audit to public organizations and private: a systematic review of the literature - Aldinete de Almeida Reinaldi, Maria; Lucas Fraga Sebastião, Argeu; Danrlei de Freitas Aguiar, Paulo; Cesar Garcia Freitas, Carlos (Seven Editora, 2023)
This study aimed to analyze the relevance of Internal Audit (IA) as a management support mechanism in different organizations, given the need for reliable and useful information for decision-making in the context of globalization and increasing competitiveness. To this end, a systematic review of the literature was carried out, based on the Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel of the Ministry of Education (CAPES/MEC) from 2016 to 2020. From a universe of 675 surveyed, 45 studies were identified, which showed the important role of AI for the maintenance and growth of the organizations object of analysis of these. Divided into two categories of analysis, the studies aimed at private companies have shown that AI is relevant due to the need to overcome managerial challenges, to achieve goals, to prevent fraud, to achieve the purposes of corporate governance and, consequently, to attract new investors. On the other hand, studies aimed at public institutions showed that AI is relevant due to the possibility of optimizing the use of public resources, greater transparency in the rendering of accounts to society and in the fight against corruption. DOI: 10.56238/pacfdnsv1-013